Dual-emission fluorescent sensor based on AIE organic nanoparticles and Au nanoclusters for the detection of mercury and melamine1. Issue 18 (14th May 2015) - Niu, Caixia; Liu, Qiuling; Shang, Zhehai; Zhao, Liu; Ouyang, Jin
<x xml:space="preserve">Abstract</x> A dual-emission ratiometric fluorescent sensor based on AIE organic nanoparticles and Au NCs was prepared by electrostatic interaction. The probe can detect Hg2+ and melamine not only visually but quantitatively.